The Effect of RADEC Learning Model on Student Learning Activities and HOTS on Science Learning in Elementary Schools - Deni Okta Nadia; Solfema Solfema; Yalvema Miaz; Ardipal Ardipal (Jurnal Penelitian Pendidikan IPA, 2023)
This research was motivated by the low levels of learning activities and higher-order thinking skills (HOTS) among students in science education. The study aims to determine the impact of the RADEC learning model (Read, Answer, Discuss, Explain, and Create) on the learning activities and HOTS of fourth-grade elementary school students. The research design used is experimental research with a Quasi-Experimental design that employs a Non-equivalent Control Group Design. The study's population comprises fourth-grade elementary school students, with class IVA selected as the experimental group and class IVB as the control group at SDN 09 Simpang Tigo, using simple random sampling. The instruments used in this study include questionnaires and tests. Questionnaires assess student learning activities, while tests evaluate students' HOTS. The study results revealed: (1) The Sig value (2-tailed) 0.001 < 0.05. Consequently, H0 is rejected, and H1 is accepted, indicating that the RADEC learning model influences student learning activities in social studies in fourth-grade elementary schools. (2) The Sig value (2-tailed) 0.000 < 0.05. Therefore, H0 is rejected, and H1 is accepted, demonstrating that the RADEC learning model has an impact on students' HOTS in science education in fourth-grade elementary schools. In conclusion, the study findings suggest that the RADEC learning model significantly influences students' learning activities and high-order thinking skills in science education in fourth-grade elementary schools.